Model Prediksi Pelanggaran Akuntansi - Octaviana Dian Ayuningrum; Tumirin Tumirin (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
Financial statements are a reflection of the condition of a company in a certain period. Financial statements are said to be good if the report can provide transparent information and explanations about the results of operations or activities based on predetermined rules. However, there are still many deviations in accounting (accounting irregularities) by companies to maintain and increase the value of the company in attracting investors to keep investing their funds for the survival of the company. These actions included fraud in intentional financial statements. This can be detrimental to users of financial statements in making decisions. This study aims to predict of financial statement fraud with financial stability, personal financial need, ineffective monitoring, external pressure. In this study 53 samples were selected based on the purposive sampling method.This study uses a logistic regression analysis method. The results show that: Financial Stability and personal financial need can predict financial statement fraud. The results of this study are expected to provide knowledge and contribution to the development of the science of triangle fraud. And provide additional information about the factors that can affect a company fraudulent in the financial statements.